Type II & III inhibitors of tropomyosin receptor kinase (Trk): a 2020-2022 patent update - Iliev, Petar; Jaworski, Carolin; Wängler, Carmen; Wängler, Björn; Page, Brent D. G.; Schirrmacher, Ralf; Bailey, Justin J. (Expert opinion on therapeutic patents, 2024)
The Trk family proteins are membrane-bound kinases predominantly expressed in neuronal tissues. Activated by neurotrophins, they regulate critical cellular processes through downstream signaling pathways. Dysregulation of Trk signaling can drive a range of diseases, making the design and study of Trk inhibitors a vital area of research. This review explores recent advances in the development of type II and III Trk inhibitors, with implications for various therapeutic applications. Patents covering type II and III inhibitors targeting the Trk family are discussed as a complement of the previous review, Type I inhibitors of tropomyosin receptor kinase (Trk): a 2020-2022 patent update. Relevant patents were identified using the Web of Science database, Google, and Google Patents. While type II and III Trk inhibitor development has advanced more gradually compared to their type I counterparts, they hold significant promise in overcoming resistance mutations and achieving enhanced subtype selectivity - a critical factor in reducing adverse effects associated with pan-Trk inhibition. Recent interdisciplinary endeavors have marked substantial progress in the design of subtype selective Trk inhibitors, with impressive success heralded by the type III inhibitors. Notably, the emergence of mutant-selective Trk inhibitors introduces an intriguing dimension to the field, offering precise treatment possibilities.
Online veröffentlicht: 30. Mai 2024
Gesehen am 15.01.2025